Eccessi di vita: autobiografismi tra risonanza e marginalità (Altre Modernità, 2020)
Although memoirs, confessions and diaries have gained huge popularity, life writing’s definition and values are not completely consolidated, as suggested by the unlimited discussion of autobiography and the different forms this genre can acquire. Moreover, since more and more non-professional authors have been publishing narratives about themselves, critics still tend to neglect these texts, which they often consider naïf and rough. This essay seeks to shed light on the dynamic mechanisms which exclude or include life writing in the literary realm. Aspects such as the influence of canonical autobiographies, the selective processes and the function of narrativity and will be scrutinized as well. The corpus will not only focus on texts by well-known authors (Annie Ernaux, Hervé Guibert), but also on works by ‘one hit wonders’ autobiographers (Fritz Zorn, Lucy Grealy).